Point-of-Care NSE Biosensor for Objective Assessment of Stroke Risk - Cheng Hsu Chen; Erick Wang; Tsung-Han Lee; Cheng-Chieh Huang; Chun-San Tai; Yan-Ren Lin; Wen-Liang Chen (Biosensors)
The rapid identification of stroke is critical to improving stroke patient outcomes. Existing protocols for assessing the risk of stroke are subjective and may be further complicated by nonspecific symptoms, increasing the risk of misdiagnosis. Neuron-specific enolase (NSE) has emerged as a promising stroke biomarker. However, current detection methods such as the electrochemiluminescence immunoassay (ECLIA) are time-consuming and costly. In this research, we developed an electrochemical biosensor for the rapid quantification of NSE in whole blood. Mouse stroke models were established, and blood samples collected were analyzed using both hospital-standard ECLIA as well as the biosensor. The biosensor limit of detection was 1.15 ng/mL. NSE measurements were highly correlated between the two methods and were obtained in 5 min using 20 μL of unprocessed whole blood samples. Notably, the biosensor could accurately quantify elevated blood NSE blood that was associated with more severe stroke. Our results demonstrate the utility of the proposed biosensor in pre-hospital settings. Combined with existing stroke assessment methods, the biosensor may enable emergency personnel to identify stroke risk with greater accuracy to optimize the chances of receiving necessary treatment within the effective window.